Elucidating the Effects of Land Cover and Usage on Background Escherichia coli Sources in Edge‐of‐Field Runoff. Issue 6 (1st November 2019) - Gregory, Lucas F.; Harmel, R. Daren; Karthikeyan, Raghupathy; Wagner, Kevin L.; Gentry, Terry J.; Aitkenhead‐Peterson, Jacqueline A.
Abstract : Escherichia coli contamination in surface water is a universal issue that signifies potentially increased human health risks from fecal loading. Nonpoint‐source contamination contributes to instream fecal loading; however, land use and land cover can alter its effects on stream water quality. Different land uses and land covers yield various landscape factors that influence water quality. This study evaluated E. coli occurrence, movement, and distribution by monitoring soil and rainfall runoff from small, ungrazed, upland watersheds under native prairie, managed hay pasture, and cultivated cropland uses and land covers. Management strategies applied to each small watershed excluded anthropogenic E. coli input, thus yielding E. coli concentrations that are considered background sources. Significant differences in median E. coli loads in runoff were identified (1.47 × 10 9 –5.71 × 10 9 ) despite similar runoff volume among watersheds, suggesting that land use and land cover differences can significantly affect background pollutant load transport during runoff events. Estimated soil‐derived E. coli loads were significantly less (≤0.0046%) than runoff loads, suggesting that recent fecal deposition is likely the primary source of E. coli loading in surface runoff. Results further demonstrate the complexity in understanding watershed E. coli fate and transport and highlight the challenges in modeling, managing, and assessing background and other nonpoint‐source E. coli loads. Core Ideas: Land use and land cover differences can affect E. coli concentrations and loads. Upland soils were not a significant contributor of E. coli in surface runoff. Wildlife can contribute significant E. coli loading in edge‐of‐field runoff.